Kemampuan Beneish M-Score Dalam Memprediksi Fraudulent Financial Reporting - Puspitha, Made Yessi; Diantini, Ni Nyoman Ayu (E-Jurnal Akuntansi, 2023)
The aim of this research is to determine the ability of the Beneish M-Score model to predict fraudulent financial reporting in banking companies in Indonesia. The research was conducted on all banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method of determining the sample using a non-probability method with purposive sampling technique. The data analysis technique used is discriminant analysis. The results showed that the Beneish M-Score was able to predict fraudulent financial reporting. The practical implication of this research is that investors can consider the Beneish M-Score before making economic decisions. The Beneish M-Score analysis can be an indication (red flag) of a company committing fraudulent financial reporting. Keywords: Fraudulent Financial Reporting; Beneish M-Score; Discriminant Analysis